Antimicrobial and Genetic Profiles of Vibrio vulnificus and Vibrio parahaemolyticus Isolated From the Maryland Coastal Bays, United States - da Silva, Ligia V.; Ossai, Sylvia; Chigbu, Paulinus; Parveen, Salina (Frontiers in Microbiology, 2021)
Vibrio vulnificus and V. parahaemolyticus, found naturally in marine and estuarine environments, are the leading cause of seafood associated gastrointestinal illness and death. Consumption of improperly cooked crabs and handling of live crabs are potential routes of exposure to pathogenic bacteria such as V. vulnificus and V. parahaemolyticus. Little information is available on serotype genetic and antimicrobial profiles of V. vulnificus and V. parahaemolyticus recovered from Maryland estuaries. The aim of the present study was to determine the serotype of V. parahaemolyticus, evaluate antimicrobial susceptibility and genetic profiles of V. vulnificus and V. parahaemolyticus isolated from water and blue crab (Callinectes sapidus) samples collected from the Maryland Coastal Bays. One hundred and fifty (150) PCR confirmed V. parahaemolyticus including 52 tdh+ (pathogenic) and 129 V. vulnificus strains were tested for susceptibility to twenty (20) different antibiotics chosen by clinical usage for Vibrio species. The O serogroups were determined using an agglutination test with V. parahaemolyticus antisera. Pulsed-field gel electrophoresis (PFGE) was used for molecular subtyping to investigate the genetic diversity among tested strains. The most prevalent serotypes were O5 (33.3%), O3 (18.7%) and O1 (14.7%). More than 41% of all tested Vibrio isolates were resistant to three or more antibiotics. Cephalothin showed the highest resistance (42% and 61%), followed by cefoxitin (42% and 31%) and ceftazidime (36% and 29%) for V. vulnificus and V. parahaemolyticus, respectively. Most strains (99–100%) were susceptible to ampicillin/sulbactam, levofloxacin, piperacillin, piperacillin/tazobactam, and tetracycline. Fifty percent (50%) of the cephalothin resistant strains were crab isolates. Vibrio vulnificus and V. parahaemolyticus isolates demonstrated a high genetic diversity and 31% of V. vulnificus and 16% of V. parahaemolyticus strains were PFGE untypeable. No correlations were found between the V. parahaemolyticus serotype, pathogenicity, genetic and antimicrobial resistance profiles of both species of Vibrio. The observed high multiple drug resistance of V. vulnificus and V. parahaemolyticus from blue crab and its environment is of public health concern. Therefore, there is a need for frequent antibiotic sensitivity surveillance for Vibrio spp.